2013
DOI: 10.2310/8000.2013.130847
|View full text |Cite
|
Sign up to set email alerts
|

Utility of computed tomography and derivation and validation of a score to identify an emergent outcome in 2,315 patients with suspected urinary tract stone

Abstract: Objective: Because a majority of urinary tract stones (UTSs) pass spontaneously and clinically significant alternative pathology is rare, we hypothesize that many computed tomographic (CT) scans to diagnose them are likely unnecessary. We sought to measure the impact of renal CT scans on resource use and to justify a prospective study to derive a score that predicts an emergent diagnosis in patients with suspected UTS by doing so in our retrospective series. Methods: We conducted a retrospective study of ED pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Utilization of point‐of‐care ultrasound (POCUS) can be used in acute settings to rapidly rule in the diagnosis of renal colic and to avoid nonselective, standard‐dose CT scan examination for all renal colic patients . It has been suggested that ultrasound‐first approach can avoid radiation exposure in about 70% of cases . In a large multicenter, randomized trial, the initial ultrasound approach was found to be noninferior to the CT scan–first approach, when compared for the rates of complications, serious adverse events, or hospitalizations .…”
mentioning
confidence: 99%
“…Utilization of point‐of‐care ultrasound (POCUS) can be used in acute settings to rapidly rule in the diagnosis of renal colic and to avoid nonselective, standard‐dose CT scan examination for all renal colic patients . It has been suggested that ultrasound‐first approach can avoid radiation exposure in about 70% of cases . In a large multicenter, randomized trial, the initial ultrasound approach was found to be noninferior to the CT scan–first approach, when compared for the rates of complications, serious adverse events, or hospitalizations .…”
mentioning
confidence: 99%
“…The CT images obtained from their study revealed that out of 2331 patients, 49 patients (2.2 %) had an emergency result, and 239 patients (10.6%) underwent urological surgery within 8 weeks after receiving CT. The presence of abdominal pain, the number of WBCs, the RBCs in the urine, and the maximum temperature were the primary predictors of the first result 16 . However, a study conducted in 2020 by Seyed Mohammad Hosseini Nejad et al with the purpose of assessing the consequences and determinant factors of invasive intervention and readmission in patients with renal colic.…”
Section: Discussionmentioning
confidence: 98%
“…Алгоритми із застосуванням методів ехографії та доплерографії дозволяють значною мірою прискорити та спростити процес обстеження пацієнтів з симптомами ниркової коліки, легко диференціювати урологічні, гострі хірургічні, гінекологічні захворювання, виявити конкременти у сечоводі хворого, визначити наявність порушень уродінаміки, що потребують ургентної застосування рентгенологічних та інвазивних методик [9][10][11].…”
Section: загальна хірургія (всі хірургічні дисципліни)unclassified